The Public-Private Partnership as Legal Instrument in the State and Regional Property Management: Challenges and Development - Muhammad Ilham Arisaputra; Irwansyah Irwansyah; Anshori Ilyas; Ahsan Yunus (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2022)
This research aims to know the dynamics of the development of people’s lives are getting more advanced and the government's burden as the government administrator is increasing. This research is legal research using the statutory and conceptual approaches. This paper provides information on the latest trend in research. The results show that all State or regional property is used to maximize public services. Even some State/regional properties should be able to be enjoyed by the public. The existence of the Government and Private Entity Cooperation as one of the legal figures, which is a model of cooperation financing for the provision of infrastructure for State/regional property, in the end, actually raises legal problems related to its management. The conclusion show that the most important problem is the Government and Private Entity Cooperation, the potential for merging of public and private affairs that may participate in the provision of commercial facilities. Ideally, the Government and Private Entity Cooperation are intended to provide social and economic infrastructure in the context of public services.